2014
DOI: 10.1016/j.resp.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

On locating the obstruction in the upper airway via numerical simulation

Abstract: The fluid dynamical properties of the air flow in the upper airway (UA) are not fully understood at present due to the three-dimensional (3D) patient-specific complex geometry of the airway, flow transition from laminar to turbulent and flow-structure interaction during the breathing cycle. It is quite difficult at present to experimentally measure the instantaneous velocity and pressure at specific points in the human airway. On the other hand, direct numerical simulation (DNS) can predict all the flow proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 34 publications
(47 reference statements)
1
32
0
Order By: Relevance
“…Direct numerical simulation (DNS) does not require any turbulence models to resolve turbulent fluctuations if the time and length scales used are small enough and is often considered as the gold standard in numerical simulations. However, the high computational cost limits its applications, and very limited studies can be found in the literature for both simplified geometries (Lin et al, 2007; Varghese et al, 2007) and human nasal cavity (Wang and Elghobashi, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Direct numerical simulation (DNS) does not require any turbulence models to resolve turbulent fluctuations if the time and length scales used are small enough and is often considered as the gold standard in numerical simulations. However, the high computational cost limits its applications, and very limited studies can be found in the literature for both simplified geometries (Lin et al, 2007; Varghese et al, 2007) and human nasal cavity (Wang and Elghobashi, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The number of control volumes for this case was 148 million. Recently, Wang and Elghobashi (2014) have solved the nose cavity with a short upper part of the trachea and with a very limited length of the laryngeal jet using the DNS-lattice Boltzmann. They solved steady inflow and outflow (not the breathing cycle) and the model contained 208 million voxels.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) was performed on the 3D surface model using previously described methods20. Briefly, CFD results were calculated using a custom developed 3-dimensional solver based on the direct numerical simulation lattice Boltzmann methods (DNS-LBM).…”
Section: Resultsmentioning
confidence: 99%
“…The imaging probe incorporated a position sensor to record the location of each cross-sectional scan, which is crucial for the generation of three dimensional models of the complex upper airway shape. Using these structural models, computational simulations can be performed to provide physicians a better understanding of airflow within the upper airway19202122. The first high speed in vivo imaging of human upper airway with integrated position tracking was demonstrated.…”
mentioning
confidence: 99%